Implementation of Augmented Reality Media Use on Mathematics Problem Solving Ability of Elementary School Students - Siti Musyarrofah (CV. Akademi Merdeka, 2024)
This study aims to explore the implementation of augmented reality (AR) media in improving elementary school students' mathematical problem solving ability. The study involved students from several classes who were divided into experimental groups using AR media and control groups using conventional methods. The results of the analysis showed that the use of AR can improve the understanding of mathematical concepts and student engagement in the learning process. Although the difference in scores between the two groups was not statistically significant, there were indications of improvement in the experimental group. These findings highlight the importance of developing innovative learning media such as AR to support the mathematics education process at the primary level.